Genetic mechanisms of bone digestion and nutrient absorption in the bone-eating worm Osedax japonicus inferred from transcriptome and gene expression analyses. Issue 1 (December 2017) - Miyamoto, Norio; Yoshida, Masa-aki; Koga, Hiroyuki; Fujiwara, Yoshihiro
Abstract Background Bone-eating worms of the genusOsedax (Annelida, Siboglinidae) have adapted to whale fall environments by acquiring a novel characteristic called the root, which branches and penetrates into sunken bones. The worms lack a digestive tract and mouth opening, and it has been suggested thatOsedax degrade vertebrate bones and uptake nutrients through acidification and secretion of enzymes from the root. Symbiotic bacteria in the root tissue may have a crucial role in the metabolism ofOsedax . However, the molecular mechanisms and cells responsible for bone digestion and nutrient uptake are still unclear, and information on the metabolic interaction betweenOsedax and symbiotic bacteria is limited. Results We compared transcriptomes from three different RNA samples from the following tissues: trunk + palps, root + ovisac, and larva + male. A Pfam domain enrichment analysis revealed that protease- and transporter-related genes were enriched in the root + ovisac specific genes compared with the total transcriptome. Through targeted gene annotation we found gene family expansions resulting in a remarkably large number of matrix metalloproteinase (mmp ) genes in theOsedax compared with other invertebrates. Twelve of theseOsedax mmp genes were expressed in the root epidermal cells. Genes encoding various types of transporters, including amino acid, oligopeptide, bicarbonate, and sulfate/carboxylate transporters, were also expressed in root epidermal cells. In addition, amino acid and other metabolite transporter genes were expressed in bacteriocytes. These protease and transporter genes were first expressed in root tissues at the juvenile stage, when the root starts to develop. Conclusions The expression of various proteinase and transporter genes in the root epidermis supports the theory that the root epidermal cells are responsible for bone digestion and subsequent nutrient uptake. Expression of transporter genes in the host bacteriocytes suggests the presence of metabolic interaction betweenOsedax and symbiotic bacteria.